Asymmetric Adaptation to Heat and Energy Poverty - Camacho, Adriana (2026)
We study the responses of household electricity consumption to temperature changes, focusing on asymmetries between welfare deciles. Our analysis exploits a unique panel dataset for Peru that links household survey microdata with repeated administrative records on energy use and local temperature. Using fixed-effects models, we estimate how electricity consumption varies with temperature, highlighting the unequal capacity of households across income deciles to adapt to climate change. Based on this evidence, we propose and implement a novel measure of adaptive energy poverty, which captures households’ ability to respond to rising ambient temperatures through increased elec- tricity consumption.